ChemInform Abstract: Novel 1, 4‐Substituted‐1, 2, 3‐Triazoles as Antitubercular Agents. Issue 35 (September 2015) - Altimari, Jarrad M.; Hockey, Samantha C.; Boshoff, Helena I.; Sajid, Andaleeb; Henderson, Luke C.
Abstract A series of 1, 4‐disubstituted triazoles (II) is synthesized via click chemistry and evaluated as potential antitubercular agents.